Peran Pengungkapan Aset Biologis dalam Memediasi Hubungan Profitabilitas, Ukuran Perusahaan, dan Penilaian Perusahaan - Egnes, Egnes; Josephino, Mavrict; Sudirman, Sudirman; Angelica, Jecelyn; Suhardjo, Iwan; Meiliana, Meiliana (E-Jurnal Akuntansi, 2023)
The aim of the research is to empirically prove the influence of profitability, company size, and disclosure of biological assets on company valuation. The method used in research is a quantitative method. The sample in this research was 96 observations of agricultural companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2022 period. Research testing and analysis uses descriptive analysis methods and analytical analysis with multiple linear regression. Based on the test results, profitability has no effect on company assessment. Meanwhile, company size and disclosure of biological assets influence company valuation. Testing the role of biological asset disclosure as a mediating variable found that biological asset disclosure was able to mediate the relationship between company size and company valuation but was unable to mediate the relationship between profitability and company assessment. Keywords: Profitability; Firm Size; Biological Asset; Firm Valuation; PSAK 69